Optimization of low carbon steel coating with corrosion inhibitor method based on siwalan (Borassus flabellifer) fiber extract - Siti Khoirunnisa; Fawaid Syamsul Arifin; Nadia Erlina Mayangsari; Indra Setiawan; Evi Susanti (Departemen Teknik Kimia Fakultas Teknik Universitas Gadjah Mada, 2023)
Siwalan fiber waste (SFW) has the potential as a source of lignin (7-25%) which is used as a green inhibitor to inhibit the corrosion rate of low carbon steel (LCS). The aims of this study were: (1) determine the optimum conditions (types of HCl and H2SO4, Cinhibitor and Cmedia, inhibition temperature, and coating time) for LCS coating process using the inhibitory method using lignin extract from SFW, and (2) knowing the resistance of LCS coated with inhibitor at optimum conditions. Empirical research through laboratory experiments explains the relation between variables by analyzing numerical data. 185g of SFW produced 52.289g (28.26%) fine brown powder. IR spectrum analysis on extract showed the wavelength was almost the same as the standard. IR spectrum analysis was also carried out on the extracted compounds that were adsorbed, and the absorption peaks confirmed the presence of lignin in the adsorbed compounds. Based on the results of the analysis of the weighing data of the specimen before and after inhibition, the inhibitor concentration of 0.2–0.3 g/L in H2SO4 at 313K is the optimum condition to suppress the corrosion rate on the surface of LCS by 76.2%.